1995
DOI: 10.1002/path.1711760405
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of oncogenic antigen 519 (OA‐519) expression and proliferative activity detected by antibody MIB‐I in node‐negative breast cancer

Abstract: The prognostic value of oncogenic antigen 519 (OA-519) expression and tumour proliferative activity was evaluated in a retrospective series of 118 patients with low-risk breast cancer. Low risk was defined as negative axillary nodes, tumour diameter < or = 50 mm, and no histological evidence of invasion of skin or deep fascia (= T1N0M0 and T2N0M0). The median follow-up time was 104 months (range 5-143 months). Immunohistochemical analysis of OA-519 expression was performed on formalin-fixed, paraffin-embedded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 33 publications
5
61
0
Order By: Relevance
“…A difference in the prognostic value of MIB-1 for nodenegative and node-positive patients could be explained by more susceptibility for adjuvant (chemo)therapy in node-positive patients with high MIB-1 labelling index, whereas node-negative patients were not treated by adjuvant systemic therapy. The median percentage of MIB-1-positive cells in our patients (7%) tended to be lower than the median value of 16-20% reported from several other studies (Jensen et al, 1995;Domagala et al, 1996;Veronese et al, 1996), but is comparable with the median value of two other reports (Keshgegian et al, 1995;Ellis et al, 1996). For Ki-67 as measured in frozen sections quite different median values varying from 2% (Brown et al, 1996) to 12% (Bouzubar et al, 1989) are also reported.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…A difference in the prognostic value of MIB-1 for nodenegative and node-positive patients could be explained by more susceptibility for adjuvant (chemo)therapy in node-positive patients with high MIB-1 labelling index, whereas node-negative patients were not treated by adjuvant systemic therapy. The median percentage of MIB-1-positive cells in our patients (7%) tended to be lower than the median value of 16-20% reported from several other studies (Jensen et al, 1995;Domagala et al, 1996;Veronese et al, 1996), but is comparable with the median value of two other reports (Keshgegian et al, 1995;Ellis et al, 1996). For Ki-67 as measured in frozen sections quite different median values varying from 2% (Brown et al, 1996) to 12% (Bouzubar et al, 1989) are also reported.…”
Section: Discussionsupporting
confidence: 57%
“…In this study with long follow-up, MIB-1 expression was a significant prognostic factor for disease-free survival both in univariate British Journal of Cancer (1998) (Jensen et al, 1995;Pinder et al, 1995;Domagala et al, 1996). The largest study on MIB-1 has shown a significant influence of MIB-I on both disease-free and overall survival in multivariate analysis (Seshadri et al, 1996) after a follow-up of 66 months.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Regarding OS (9472 patients), of all 35 studies, subgroup analysis was possible in nine studies with nodenegative patients (1996 patients) (Jensen et al, 1995;Weikel et al, 1995;Bevilacqua et al, 1996;Brown et al, 1996;Domagala et al, 1996;Fresno et al, 1997;Rudolph et al, 1999a;Trihia et al, 2003;Erdem et al, 2005), in four with node-positive patients (857 patients) Domagala et al, 1996;Gonzalez et al, 2003;Trihia et al, 2003) and in two that included only untreated patients (node-negative and node-positive) (284 patients) (Pinder et al, 1995;Bevilacqua et al, 1996).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…76,77 It is minimally expressed in normal tissues, but frequently upregulated in cancers, notably the hormone-sensitive breast, uterine and prostate carcinomas, with frequent correlation with poor prognosis. 78,79 SREBF1 (sterol regulatory element binding transcription factor 1), which regulates the transcription of FASN 80 is encoded by a gene also overexpressed in luminal A tumours.…”
Section: Extensive Transcriptional Differences Between Basal and Lumimentioning
confidence: 99%